The Interrelation between Local Government of Kapuas Hulu Regency and Breeders in Developing the Breeding of Super Red Arowana - Firmansyah Firmansyah; Hermin Indah Wahyuni; Alia Bihrajihant Raya (Universitas Muhammadiyah Yogyakarta, 2019)
Super Red Arowana breeding activities have the potential to be developed for community and regional improvement in Kapuas Hulu Regency. Initiatives to establish breeding activities through programs that are expected to be a source of regional income and to create suitable self supports for breeders are still experiencing some obstacles due to the lack of interaction on communication and distribution of information between the local government of Kapuas Hulu and the breeders that are not transparent, equal, and smooth. This study aimed to find the interrelation of the Kapuas Hulu local government with the breeders in the development of Super Red Arowana captivity activities and the efforts of the stakeholders in improving interrelation through communication accommodation studies. This study uses a qualitative method for explanative purposes. The results showed that a problem in the internal environment Kapuas Hulu local government and the breeder impinge on the interrelation of them. The efforts of both parties in improving interrelation through joint media have not shown adequate results due to the lack of full and mutual recognition. The local government of Kapuas Hulu and the breeders in the process of accommodating communication have adopted not only convergence but also divergence adaptation.